2002
DOI: 10.1034/j.1600-0412.2002.810910.x
|View full text |Cite
|
Sign up to set email alerts
|

Reference range for cervical length in twin pregnancies

Abstract: Cervical length shortens gradually throughout gestation in twin pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
0
15
1
3
Order By: Relevance
“…Preterm birth occurs in more than 50% of twin gestations . In São Paulo state, in 2012, twin pregnancies contributed for 14.80 and 11.8% of all deliveries prior to 32 and 36 weeks' gestation, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Preterm birth occurs in more than 50% of twin gestations . In São Paulo state, in 2012, twin pregnancies contributed for 14.80 and 11.8% of all deliveries prior to 32 and 36 weeks' gestation, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…The values of canal length at 16-19 weeks' gestation in both singleton and non-tocolysis twin pregnancies are similar to other reports at the corresponding gestational age in singleton as well as twin pregnancies. 14,15,19 In cases of preterm delivery at <36 weeks and preterm labor in twin pregnancies, we observed a different pattern in canal length shortening, compared with non-tocolysis twin pregnancies as well as normal singleton pregnancies. The canal length in twin pregnancy with preterm labor and delivery at 16-19 weeks was significantly shorter than that of non-tocolysis twin pregnancies.…”
Section: Discussionmentioning
confidence: 69%
“…Our results are inconsistent with other reports, which demonstrated that canal length shortened linearly with advancing gestational age up to term. 15,16 This inconsistency may be due to the difference in analytical methods. In our study, the observational period of 16-35 weeks was stratified into five gestational age groups and comparisons were made between age groups, whereas other studies showed the relationship between canal length and gestational age by linear regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In normal pregnancies, as gestational age increases, gradual reduction of cervical length can be observed (19)(20)(21)(22). Similar to twin pregnancies, polyhydramnios can lead to shortening of the cervix with uterine distension (7).…”
Section: Discussionmentioning
confidence: 99%